PENDAMPINGAN MASYARAKAT DALAM UPAYA MENINGKATKAN KESADARAN HUKUM TENTANG HAK MILIK ATAS TANAH MELALUI SISTEM PENDAFTARAN TANAH DI DESA ANDAMAN KECAMATAN ANJIR PASAR KABUPATEN BARITO KUALA - Hanafi; Nahdhah; Muhammad Syahrial Fitri (Scholar Center, 2021)
The development is getting more advanced, placing land in an important aspect in society which is increasingly dynamic as it is today, so that legal certainty is an important factor. We will get the terms of ownership if we register a plot of land in question with the government. There are several ways of registering land that we can take, namely,